Rulisca: Science learning media for elementary school students - Ari Suryawan; Evalina Evalina; Novi Wulandani (Community Empowerment, 2024)
A crucial responsibility of teachers lies in fostering innovative learning processes. Meaningful learning experiences facilitate students' comprehension of the subject matter. Consequently, the need arises for instructional media to serve as teaching aids, cultivating an engaging learning environment for students. The core concept of instructional media lies in facilitating students' understanding from abstract to concrete concepts. Its primary functions include serving as a learning resource, providing information and knowledge to students. Furthermore, instructional media can motivate learning, reinforce previously learned material, and stimulate students. One such innovative tool is the "rumah listrik cahaya" (Rulisca). Rulisca's design is rooted in the instructional media needs of science education and the psychological conditions of phase B or fourth graders in elementary schools. This medium is specifically tailored for the topic of energy transformation. During its implementation, students are guided to comprehend the relationship between solar panels and LED lights, enabling them to grasp the concrete process of energy transformation.